1995
DOI: 10.1128/aac.39.12.2615
|View full text |Cite
|
Sign up to set email alerts
|

Use of decimal assay for additivity to demonstrate synergy in pair combinations of econazole, nikkomycin Z, and ibuprofen against Candida albicans in vitro

Abstract: Interactions between six compounds (econazole, miconazole, amphotericin B, nystatin, nikkomycin Z, and ibuprofen) were investigated for their antifungal activities against Candida albicans by using pair combinations in an in vitro decimal assay for additivity based on disk diffusion. Additive interactions were observed between miconazole and econazole, amphotericin B and nystatin, and amphotericin B and ibuprofen, while an antagonistic interaction was observed between econazole and amphotericin B. Synergistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…Also, methods for the interpretation of kill-kinetic studies vary, and synergy has been defined by some authors as at least a 100-fold increase in killing at 24 h (Bonapace et al, 2000;Jung et al, 2004;Kiraz et al, 2009;Mayer and Nagy, 1999), while other authors consider a 200-fold increase (Guo et al, 2008;Leonard, 2012;Tan et al, 2011). Relatively to checkerboard, the endpoint (i.e., the complete inhibition of growth) is a qualitative measure (Tariq et al, 1995), and the occurrence of synergy appears to be highly dependent on the method of interpretation (Bonapace et al, 2002). Also, the reproducibility of checkerboard is hardly the best.…”
Section: Discussionmentioning
confidence: 99%
“…Also, methods for the interpretation of kill-kinetic studies vary, and synergy has been defined by some authors as at least a 100-fold increase in killing at 24 h (Bonapace et al, 2000;Jung et al, 2004;Kiraz et al, 2009;Mayer and Nagy, 1999), while other authors consider a 200-fold increase (Guo et al, 2008;Leonard, 2012;Tan et al, 2011). Relatively to checkerboard, the endpoint (i.e., the complete inhibition of growth) is a qualitative measure (Tariq et al, 1995), and the occurrence of synergy appears to be highly dependent on the method of interpretation (Bonapace et al, 2002). Also, the reproducibility of checkerboard is hardly the best.…”
Section: Discussionmentioning
confidence: 99%
“…However, a more extensive study of the drug kinetics and of other strains of the same and other related species (Encephalitozoon cuniculi, Encephalitozoon intestinalis) is required. Our results also indicate the need to test this drug on these protozoa in combination with other chemotherapeutic agents, namely, azole derivatives, on the basis of recent successfully performed studies against some chitinous fungi (1,14,20).…”
Section: Discussionmentioning
confidence: 99%
“…3,16 Here, combinations of amphotericin B and azoles mostly resulted in indifferent interactions against C. dubliniensis in both groups of isolates.…”
Section: Brief Communicationmentioning
confidence: 99%
“…most commonly evaluated in the majority of in vitro antifungal combination studies. While the combination of azoles with amphotericin B has provided controversial results, 3 most of studies have found additive or synergistic effect when azoles were combined with terbinafine against C. albicans. [4][5][6] Other Candida spp.…”
mentioning
confidence: 99%